Tourism as a contribution to the advancement of capital in village Itaúnas/ES and culture as expression of resistance - Xavier, Maria A. de Sá; Bassetti, Telma Bitencourt (Geografares, 2016)
The article discusses how the tourism contribution to the advancement of capital, focusing on traditional community of Vila Itaúnas. We aim reflection, followed by discussion about the local culture while resistance deployment process hegemonic tourism sun and sea. We use exploratory methodology and survey of topics relevant to the discussion, followed by rereading etnogeográfica research, and its empirical data used for analysis, and after discussing the issue. We argue Ticumbi as the local Social Institution without tourist appropriation, there is however necessary elements for the formation of productive arrangements of community basis stations in your everyday organizational spatiality. Keywords: Tourism, Cultural Resistance, Village Itaúnas.